Do Cachimbo à Gabardine: O Mito do Detetive em Sherlock Holmes e Philip Marlowe - Sottomayor, João (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Both Sherlock Holmes and Philip Marlowe are a product of their time and reflect the ideas of their authors regarding the societies they were a part of. Curiously, whereas Holmes generally validates and defends the Victorian status quo, Marlowe considers American society to be corrupt. However, due to both men's moral values, as well as their identification with their trade, they represent models of conduct, which attributes to them a mythical quality.